RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN KARYAWAN “BONITA ART & DESAIN INTERIOR” - Fuad Azril Syamil Bayasef; Kemal Khairul Biqa; Alpan Hidayat; Perani Rosyani (CV. Multi Kreasi Media, 2022)
Payroll information system is one of the systems needed in a company. Bonita Art (CV) is a business entity engaged in interior design and furniture services. In CV. Bonita Art payroll still uses the conventional system, namely salaries are calculated manually using Microsoft Excel and employee data storage only uses Microsoft Word. This is considered less effective because it is vulnerable to losing employee data and monthly payroll reports. The purpose of the researcher is to develop a system that can make it easier for admins to sort payroll to make it easier for admins to see expenses every month. The development of this information system uses Netbeans IDE 8.2 software and PHP myadmin with the result that the system has been running well and is suitable for use, namely with a desktop system. Bonita Art and Interior Design can help manage employee payroll data.